Implications of Ripening Inhibiting Mutant Gene (RIN) in Different Quantitative and Qualitative Characters of Tomato - Mukhia, Dibya Jyoti; Karak, Chandan; Hazra, Pranab (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted comprising of four widely divergent genetic materials of tomato viz. BCT- 111 rin possessing specific mutant genes and CLN B, Patharkutchi, BCT-53 are normal lines without possessing specific genes in Central Research Farm, Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India during autumn-winter (2018‒19 to 2019‒20) aimed to evaluate genotype level variation due to rin gene in both homozygous and heterozygous condition for different characters. Three hybrids viz. BCT-111 rin×CLN B, BCT-111 rin×Patharkuchi, BCT-111 rin×BCT-53 were developed involving BCT-111 rin and normal 3 genotypes. The seven genotypes including the parental lines and hybrids exhibited wide range of variations in different traits namely, plant height (84.59‒106.94 cm), number of days to first flowering after transplanting (25.7‒41.26), number of flower clusters plant-1 (18.21‒25.69), number of flowers cluster-1 (5.73‒8.48), number of fruits plant-1 (49.22‒76.02), fruit weight (37.89‒97.50 g), equatorial diameter (24.71‒52.60 mm), polar diameter (26.00‒47.81 mm), locule number fruit-1 (2.48‒3.96), pericarp thickness (4.94‒6.84), fruit yield plant-1 (2.93‒4.07 kg), total soluble solids (3.95‒6.21° brix), total sugar content (1.43‒3.47%), reducing sugar (1.21%‒2.58%), titratable acidity (0.36%‒0.64%), ascorbic acid content (25.66‒34.76 mg 100 g-1 fresh weight), lycopene content (0.38‒4.16 mg 100 g-1 fresh weight) and β-carotene (0.24‒0.60 µg 100 g-1 fresh weight). In the genotype possessing the ripening inhibitor rin gene in homozygous condition, fruit did not ripe and lycopene biosynthesis was severely reduced. However, in heterozygous condition, lycopene biosynthesis was almost normal which amply justified the possibility of utilizing the genotype possessing ripening inhibitor rin gene for development of commercial hybrids of tomato.